Elevated levels of serum alpha-2-macroglobulin associate with diabetes status and incident CVD in type 1 diabetes - Baohai Shao; Janet K. Snell-Bergeon; Ian H. de Boer; W. Sean Davidson; Karin E. Bornfeldt; Jay W. Heinecke (Journal of Lipid Research)
Atherosclerotic CVD is a major cause of death in individuals with type 1 diabetes mellitus (T1DM). However, conventional risk factors do not fully account for the increased risk. This study aimed to investigate whether serum proteins associate with diabetes status and the occurrence of CVD in T1DM. We used isotope dilution-MS/MS to quantify 28 serum proteins in 228 subjects participating in the prospective Coronary Artery Calcification in Type 1 Diabetes study. We used linear regression to analyze the association between serum protein levels and T1DM status using 47 healthy controls and 134 T1DM patients without CVD and Cox proportional hazards regression to assess their prediction for incident CVD by a case-cohort study using a subcohort of 145 T1DM subjects and a total of 47 CVD events. Of the 28 serum proteins studied, five of them—alpha-2-macroglobulin (A2M), apolipoprotein A-IV, apolipoprotein L1, insulin-like growth factor 2, and phospholipid transfer protein—were significantly associated with T1DM status, with A2M being 1.6-fold higher in T1DM. After adjusting for potential confounders, A2M independently predicted incident CVD, with a mean hazard ratio of 3.3 and 95% CI of 1.8–6.1. In our study, A2M showed the largest increase in serum levels when comparing patients with T1DM to control subjects. A2M also predicted incident CVD, suggesting that it could serve as both a marker and possibly a mediator of atherosclerosis in T1DM. These findings emphasize the importance of specific serum proteins in assessing and managing CVD risk in T1DM.